Christian Initiation. Progressive Itinerary of Configuration with the Paschal Christ. “We are Baptisted and Confirmed in Order to the Eucharist” (SCa. 17) (Teología, 2017)
This article refers to the content of my doctoral thesis defended in the Faculty of Theology in 2014, whose title is “The Christian initiation, progressive itinerary of the configuration with Easter Christ”. A panoramic view of the arguments that are considered to be more important in the three parts of the thesis is presented in its exposition. The chapter referred to CI’s history is just an indication of the extensive trip that has been done in the thesis while the focus of this article has been placed in the theological approximation to the CI as participation in the Mystery of Christ and of the Church and as a progressive configuration through the initial moments of the Christian existence, that is to say, the sacraments of the initiation. The Eucharist is also outlined as the culmination of the CI. As regards the pastoral questionings, it mainly focuses on the controversial topic of the location of the Confirmation inside de CI. This article also supposes the current practice of the CI in the paranaense church that has recovered the so called traditional order of the sacraments, which happened during the episcopate of present Cardinal E. Karlic. It is consequently a situation as new as ancient, since the recuperation is located in the line of the eastern tradition and through with its own western characteristics.
Keywords: Christian Initiation; Christ; Church; Easter Mystery; Sacraments; Catechism; Way.